Determinan Pertumbuhan Ekonomi 34 Provinsi di Indonesia Tahun 2015-2022 - Said Muhammad Fikri; Syamsurijal Tan; Candra Mustika (JURNAL EKONOMI BISNIS DAN MANAJEMEN, 2026)
Economic growth is an important indicator of regional development performance. This study aims to analyze the conditions of economic growth, foreign direct investment (FDI), labor, the Gini ratio, and the Human Development Index (HDI) across 34 provinces in Indonesia during 2015–2022, as well as to examine the influence of these variables on economic growth. The study employs secondary panel data obtained from Statistics Indonesia (BPS) and related institutions. Data were analyzed using descriptive statistics and panel data regression. Model selection was conducted through the Chow, Hausman, and Lagrange Multiplier tests, which identified the Fixed Effect Model (FEM) as the most appropriate estimation model. The results indicate that FDI has a positive but insignificant effect on economic growth. Labor and HDI have positive and significant effects, suggesting that employment opportunities and improvements in education, health, and living standards contribute to regional economic growth. The Gini ratio also shows a positive and significant relationship with economic growth during the study period. Simultaneously, FDI, labor, the Gini ratio, and HDI significantly influence economic growth, indicating that these variables collectively explain variations in regional economic performance across Indonesian provinces.